Religiosity as a Predictor of Cheating Behavior in Junior High School Students: A Correlational Study - Ulfa Danni Rosada; Diki Herdiansyah; Khatrun Nada binti Mohamad Khadafi (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Cheating among students is a serious issue that undermines academic integrity and the quality of education. This study explores the relationship between religiosity and cheating behavior among junior high school students. Using a correlational approach, the research involved 77 students to measure religiosity levels and the frequency of cheating behaviors using scales validated for reliability and validity. Simple linear regression analysis revealed a significant effect of religiosity on cheating behavior (p < 0.05), with a 20.3% contribution. These findings indicate that higher levels of religiosity are associated with a lower tendency to cheat. The study suggests integrating character education based on religiosity into the curriculum to enhance academic integrity. Future research is recommended to explore other factors that may mediate this relationship in various cultural and religious contexts. Keywords: cheating behavior, religiosity, guidance and counseling, adolescence